(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was performed to observe the differential patterns in mineralo -physiological attributes of Sahiwal and Hariana cows during their pre-partum vaginal prolapse. During the experimental period of five months, a total of five Sahiwal and no Hariana cows were found to be suffering from pre-partum vaginal prolapse. The physiological and mineral attributes of prolapsed Sahiwal cows were compared with those of healthy Sahiwal and Hariana cows. In present study, plasma concentration of calcium and phosphorus in Sahiwal cows (6.10±0.64, 3.90±0.37 mg/dl, respectively) was found to be significantly (p<0.01) lower as compared to healthy Sahiwal (10.68± 0.64 and 7.62± 0.37mg/dl, respectively) and healthy Hariana cows (10.20± 0.64 and 7.17± 0.37mg/dl, respectively). Moreover, the plasma concentration of sodium (154.40±2.36 mEq/L) in affected Sahiwal cows was observed to be significantly (p<0.01) elevated than those in healthy Sahiwal (133.40± 2.36mEq/L) and healthy Hariana cows (135.20± 2.36 mEq/L). However, a decrease (P=0.07) in plasma concentration of sodium was only observed in affected Sahiwal cows during different stages of recovery. None of the physiological attributes were found to be affected in prolapsed cows. Thus, hypocalcaemia and hypophosphatamia during advanced stage of pregnancy in Sahiwal cows may be the tentative cause of pre partum vaginal prolapse.